ERP Selection Using Fuzzy-MOGA Approach: A Food Enterprise Case Study - Joko Ratono; Kudang Boro Seminar; Yandra Arkeman; Arif Imam Suroso (Universitas Ahmad Dahlan, 2015)
Selection of Enterprise Resource Planning (ERP) system is a complex decision-making process and one of the critical success factors (CSFs) in ERP adoption life cycle. Many ERP implementation failures are caused by improper package selection. Various approaches have been used, but not using optimization techniques. This study developed a Fuzzy-Multiobjective Genetic Algorithm (Fuzzy-MOGA) approach to optimize the quality of ERP selection criteria that complies with ISO25010 quality standard and cost. A case study was conducted on an agro-industrial company. The result shows the approach of Fuzzy-MOGA with NSGA-II method facilitate a complex decision-making for ERP selection optimally.